SUBCLINICAL INTERSTITIAL PULMONARY INJURY IN RHEUMATOID ARTHRITIS - D. V. Bestaev; L. A. Bozhyeva; A. V. Volkov; A. A. Novikov; S. I. Glukhova; E. L. Nasonov (Klinicist)
Subjects and methods. The study enrolled 61 inpatients diagnosed with RA (according to the 1987 American College of Rheumatology criteria) who were treated at the V.A. Nasonova Research Institute of Rheumatology; in so doing, high-resolution computed tomography revealed lung changes as a ground glass pattern in 15 patients, reticular striation, traction bronchoectases, and lung tissue changes as honeycomb ones in 25 patients; no lung abnormalities were found in 21 patients. DAS28 was applied to determine the inflammatory activity of RA. The RA patients underwent X-ray studies of the hand, foot, and chest, by using accordingly X-Ray unit and spiral computed tomography scanner (section thickness, 0.65 mm). External respiration function (ERF) indicators were studied with plethysmograph. IgM rheumatoid factor was measured using an immune nephelometer. Serum anti-cyclic citrullinated peptide antibodies were assayed by immunochemiluminescence technique on a Cobas e411 analyzer. The xMAP technology using a BioPlex200 analyzer was employed to determine the serum concentrations of 27 cytokines in 15 patients with subclinical IPI and in 25 with clinical IPI. Results and discussion. The major respiratory signs in patients with IPI proved to be cough (24 %), expectoration (20 %), dyspnea (16 %), and crepitation (64 %) on auscultation. Three patients with subclinical IPI were found to have crepitation on auscultation. Respiratory symptoms were absent in the RA patients without IPI. It should be noted that there are a larger number of RA patients with a high smoking index among the RA patients with IPI than among those without IPI (p < 0.05). Investigation of ERF indicators revealed a statistically significantly lower lung diffusing capacity (LDC) in the RA patients with subclinical IPI than in those without IPI (p < 0.05). Other ERF indicators showed no significant deviations of the reference values. LDC and total lung capacity appeared to be statistically significantly lower in the RA patients with clinical IPI than in those without IPI (p < 0.005 and p < 0.05, respectively). The differences in LDC failed to reach the statistical significance in the RA patients with subclinical IPI and in those with clinical IPI. Examination of cytokine concentrations revealed a tendency towards the higher levels of interleukin-7 (IL-7), IL-12, IL-13, IL-15, IL-17, and platelet-derived growth factor BB in the RA patients with subclinical IPI than in those with clinical IPI. At the same time, the differences in the concentration of vascular endothelial growth factor (VEGF) turned out to be statistically significant (p < 0.05). Moreover, the levels of IL-10, interferon-γ, and RANTES proved to be significantly higher in the patients with clinical IPI than in those with subclinical IPI (p < 0.008; p < 0.0003, and p < 0.03, respectively). Conclusion. Thus, the problem associated with the early diagnosis and timely adequate treatment of IPI in patients with RA is relevant. The preclinical form of IPI in patients with RA is associated with ground glass radiological and tomographic patterns and lower LDC values. VEGF may lay a claim to the role of a predictor of pulmonary fibrosis in the RA patients with subclinical IPI.